The Effect Of Different Types Of Ganoderma lucidum Isolates On The Growth Of Mycelium On The Growing Medium (BAGLOG) - Khusnul Khusnul; Rangga Syarif Muchamad; Amelia Amanda Putri (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2021)
The cultivation of Ganoderma lucidum (lingzhi) or G.lucidum mushrooms in Indonesia is still not widely developed. Factors that influence the success of lingzhi mushroom cultivation include the planting medium, environmental conditions, and the source of isolates. There has not been much research on lingzhi mushrooms to get superior lingzhi mushroom isolates. The aims of this study was to determine the effect of different sources of isolates on the growth of the mycelium of the Ganoderma lucidum on the growing medium (Baglog). This test was carried out using an experimental method with a completely randomized design (CRD) with the treatment of planting Ganoderma lucidum isolates from Tasikmalaya, Cianjur and Banyumas, on planting medium (baglog). Each treatment was replicated 30 times so that a total of 150 experimental units were obtained. The data obtained were analyzed by analysis of variance (one way ANOVA) and continued with Duncan's Multiple Range Test (DMRT) at an error rate of 5% and 1%. the conclusion of this study is that Ganoderma lucidum isolates from Tasikmalaya, Cianjur and Banyumas affect the diameter and growth rate of mycelium vegetatively.